(untitled) (Eurasian Journal of Learning and Academic Teaching, 2022)
In given article the speech goes about organizing the independent work, managing it, as responsible and complex work of each teacher. The purpose of this article is to study of organizing the independent work of schoolchildren and conditions of their successful realization. For consideration of given purpose we resorted to the analysis of the different directions in study of the nature of independence of learners in education, got acquainted with variety of the determinations and have realized what functions, executes independent cognitive activity of learners and why it is so important for shaping the mature personality